Effects of current treatments for trauma survivors with posttraumatic stress disorder on reducing a negative self-concept: a systematic review and meta-analysis - Liselotte Banz; Mina Stefanovic; Maria von Boeselager; Ingo Schäfer; Annett Lotzin; Birgit Kleim; Thomas Ehring (European Journal of Psychotraumatology, 2022)
Background: A negative self-concept is characterised by dysfunctional cognitions about the self and has been suggested to be a key factor involved in the development and maintenance of posttraumatic stress disorder (PTSD). In addition, the current definitions of PTSD according to DSM-5 and the new ICD-11 diagnosis of Complex PTSD (CPTSD) include aspects of negative self-concept in their diagnostic criteria. Objective: The aim of this meta-analysis was to synthesise the currently available evidence on the effects of psychological interventions for PTSD on negative self-concept. Methods: PubMed, PsychINFO, PSYNDEX, PTSDpubs and Cochrane Library were searched for randomised controlled trials (RCTs) of psychological treatments for PTSD symptoms in adults, published up to February 2021. A systematic review and meta-analysis were conducted, with risk of bias assessed by the Cochrane Risk of Bias Assessment Tool. Results: A total of 25 RCTs (N = 2585) were included in the meta-analysis. Results showed that psychological interventions significantly improve a negative self-concept with a moderate to large controlled effect size (k = 30, g = 0.67, 95% CI [0.31, 1.02], p < .001) at post-treatment. Heterogeneity between studies was large but could not be accounted for by moderators included in the current analysis, i.e. different types of interventions (e.g. with vs. without a cognitive restructuring component, trauma-focused vs. not). Conclusions: Current treatments for PTSD are effective in reducing a negative self-concept. However, more research is needed to identify moderators of this effect and identify interventions that are most effective for reducing negative self-concept.